Ozonation of 4-aminotoluene as a new method of synthesis of 4-aminobenzaldehyde – an intermediate for the production of anti-tuberculosis drugs - A. H. Halstian; A. S. Вushuiev; Ye. Yu. Vasylenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Solutizon is an original anti-TB drug that is effective in resisting mycobacteria to other anti-TB drugs, which is obtained by the interaction of thiosemicarbazone 4-aminobenzaldehyde and sodium oxymethylene sulfonate. 4-Aminobenzaldehyde is synthesized by redox conversion of 4-nitrotoluene in the presence of sodium polysulfide. The reaction is carried out in boiling alcohol, and 4-aminobenzaldehyde is separated after steam distillation with a yield of 40–50 %. However, today this method loses its practical, environmental and economic attractiveness, as it has significant disadvantages – low product yield, high reaction temperature (80–120 °C), the formation of sulfur-containing wastewater. Therefore, the development of low-temperature, environmentally friendly methods for obtaining 4-aminobenzaldehyde is an urgent task.